"DECOLONIZING FASHION IS WORK IN P R O G R E S S : INDIA STORY" - Vaibbhavi Pruthviraj Ranavaade (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The changing configurations have disrupted the socio-economic-political dimensions, compelling us to mitigate moral and ethical challenges and identifying new directions for fashion in the Indian subcontinent. These changes are evident in the sartorial choices and lifestyle of the people and the emerging industry practices. This paper concentrates on the fashion industry and aims to understand the new directions for the three core areas of the fashion industry for sustainable futures: education production and women. This paper aims to understand the decolonized approach for fashion education as this provides the conceptual and technical foundation for creating the valuable human resource and thought leaders for the future of fashion. The merits of adopting circular design and production and how it will contribute towards sustainable future of the fashion industry. This exploratory paper is based on a review of the literature, observations and case studies to understand the impact fashion education and circular-production on transnational feminism are discussed to elaborate on the new directions for each. Woman is at the core of all human pursuits, whether her role as a homemaker, a mother, a care giver and as principal human resource for the garment and fashion industry. Identifying the decolonized practice to find meaningful and dignified livelihoods in Indian fashion industry.